Stretch stress propels glutamine dependency and glycolysis in optic nerve head astrocytes - Pappenhagen, Nathaniel; Yin, Eric; Morgan, Autumn B.; Kiehlbauch, Charles C.; Inman, Denise M. (Frontiers in Neuroscience, 2022)
Glaucoma is an optic neuropathy that leads to irreversible blindness, the most common subtype of which is typified by a chronic increase in intraocular pressure that promotes a stretch injury to the optic nerve head. In rodents, the predominant glial cell in this region is the optic nerve head astrocyte that provides axons with metabolic support, likely by releasing lactate produced through astrocytic glycolysis. Our primary hypothesis is that stretching of the optic nerve head astrocytes alters their metabolic activity, thereby advancing glaucoma-associated degeneration by compromising the metabolic support that the astrocytes provide to the axons in the optic nerve head. Metabolic changes in optic nerve head astrocytes were investigated by subjecting them to 24h of 12% biaxial stretch at 1Hz then measuring the cells’ bioenergetics using a Seahorse XFe24 Analyzer. We observed significant glycolytic and respiratory activity differences between control and stretched cells, including greater extracellular acidification and lower ATP-linked respiration, yet higher maximal respiration and spare capacity in stretched optic nerve head astrocytes. We also determined that both control and stretched optic nerve head astrocytes displayed a dependency for glutamine over pyruvate or long-chain fatty acids for fuel. The increased use of glycolysis as indicated by the extracellular acidification rate, concomitant with a dependency on glutamine, suggests the need to replenish NAD+ for continued glycolysis and provision of carbon for TCA cycle intermediates. Stretch alters optic nerve astrocyte bioenergetics to support an increased demand for internal and external energy.